2015
DOI: 10.3892/etm.2015.2398
|View full text |Cite
|
Sign up to set email alerts
|

Testing of kisspeptin levels in girls with idiopathic central precocious puberty and its significance

Abstract: Abstract. The aim of this study was to explore the significance of plasma kisspeptin levels in diagnosis and therapeutic evaluation through the analysis of the kisspeptin levels of girls diagnosed with idiopathic central precocious puberty (ICPP) prior to treatment and after 6-months of treatment and those with simple premature thelarche (PT). A total of 70 girls including 24 girls diagnosed with ICPP, 21 girls with PT and 25 normal girls were enrolled in the study. ELISA analysis was conducted to detect the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 12 publications
2
26
2
Order By: Relevance
“…Some studies have had different results. The study conducted by Yang et al (2015) demonstrated that plasma kisspeptin levels were higher in ICPP girls, when compared to PT girls and normal controls, but there was no difference between PT and controls. Özgen et al (2016) reported that plasma kisspeptin levels were higher in ICPP girls, when compared to HC girls, but there was no difference between either PT and HC, or ICPP and PT.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have had different results. The study conducted by Yang et al (2015) demonstrated that plasma kisspeptin levels were higher in ICPP girls, when compared to PT girls and normal controls, but there was no difference between PT and controls. Özgen et al (2016) reported that plasma kisspeptin levels were higher in ICPP girls, when compared to HC girls, but there was no difference between either PT and HC, or ICPP and PT.…”
Section: Discussionmentioning
confidence: 95%
“…In both studies, authors suggested that basal kisspeptin level is a useful diagnostic tool in diagnosis of ICPP. Yang et al ( 6 ) reported that kisspeptin levels in ICPP patients were higher than those in patient with PT and in prepubertal controls. After 6 months of treatment with GnRHa, kisspeptin level was lower than that prior to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Kisspeptin is the most extensively studied neuropeptide in puberty and precocious puberty ( 6 , 7 , 8 ). In human, KISS1 is located on chromosome 1q32 and is detected in brain, pancreas, placenta, testis and genital tract ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, it has been noted that leptin's influence on adipose tissue affects the timing of puberty [5]. It has also been suggested that the plasma level of kisspeptin is associated with the initiation of pubertal development, and kisspeptin may serve as an important factor in the diagnosis of abnormal puberty [6].…”
Section: Introductionmentioning
confidence: 99%